Chrysanthemum (Chrysanthemum morifolium) CmHRE2-like negatively regulates the resistance of chrysanthemum to the aphid (Macrosiphoniella sanborni) - You Wang; Wanwan Zhang; Chaojun Hong; Lisheng Zhai; Xinhui Wang; Lijie Zhou; Aiping Song; Jiafu Jiang; Likai Wang; Fadi Chen; Sumei Chen (BMC Plant Biology, 2024)
Abstract Background The growth and ornamental value of chrysanthemums are frequently hindered by aphid attacks. The ethylene-responsive factor (ERF) gene family is pivotal in responding to biotic stress, including insect stress. However, to date, little is known regarding the involvement of ERF transcription factors (TFs) in the response of chrysanthemum to aphids. Results In the present study, CmHRE2-like from chrysanthemum (Chrysanthemum morifolium), a transcription activator that localizes mainly to the nucleus, was cloned. Expression is induced by aphid infestation. Overexpression of CmHRE2-like in chrysanthemum mediated its susceptibility to aphids, whereas CmHRE2-like-SRDX dominant repressor transgenic plants enhanced the resistance of chrysanthemum to aphids, suggesting that CmHRE2-like contributes to the susceptibility of chrysanthemum to aphids. The flavonoids in CmHRE2-like-overexpression plants were decreased by 29% and 28% in two different lines, whereas they were increased by 42% and 29% in CmHRE2-like-SRDX dominant repressor transgenic plants. The expression of Chrysanthemum-chalcone-synthase gene(CmCHS), chalcone isomerase gene (CmCHI), and flavonoid 3′-hydroxylase gene(CmF3’H) was downregulated in CmHRE2-like overexpression plants and upregulated in CmHRE2-like-SRDX dominant repressor transgenic plants, suggesting that CmHRE2-like regulates the resistance of chrysanthemum to aphids partially through the regulation of flavonoid biosynthesis. Conclusion CmHRE2-like was a key gene regulating the vulnerability of chrysanthemum to aphids. This study offers fresh perspectives on the molecular mechanisms of chrysanthemum-aphid interactions and may bear practical significance for developing new strategies to manage aphid infestation in chrysanthemums.